ADSORPSI ION Pb(II) DAN Cd(II) PADA ABU DASAR BATUBARA TERIMOBILISASI DITIZON - , TRI HANDAYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A research on adsorption of Pb(II) and Cd(II) ions using dithizone immobilized coal bottom ash has been conducted. This research aimed to examine the ability of dithizone immobilized coal bottom ash in Pb(II) and Cd(II) adsorption of the solution by using comparator adsorbent of activated coal bottom ash. Some adsorption parameters i.e. initial pH, adsorbent mass, adsorption kinetic and adsorption isotherm were examined in the adsorption processes. The characterization of dithizone immobilized coal bottom ash was analyzed using X-Ray Diffraction (XRD) method to describe the minerals constituent of bottom ash and crystallinity , Infra Red (IR) spectrophotometry to identify functional groups on the adsorbent and using Gas Sorption Analyzer (GSA) to determine the adsorbent porous distribution, BET specific surface area, total pore volume and average pore radius. The result showed that dithizone was successfully loaded on the active surface of coal bottom ash and the immobilization process did not significantly damage the crystallinity of bottom ash. The optimum condition of 40 mg.L -1 Pb(II) and Cd(II) adsorption for dithizone immobilized bottom ash occurred at pH 4 and pH 6 respectively with same of adsorbent mass and contact time was 0.3 g and 90 min. The adsorption kinetic parameter of Pb(II) and Cd(II) ions on activated bottom ash and dithizone immobilized bottom ash followed kinetic equation pseudo second order with rate constant value (k) on adsorption of Pb(II) obtained 0.298 g.mg -1 .min -1 for activated bottom ash and 0.309 g.mg -1 .min -1 for dithizone immobilized bottom ash . On the adsorption of Cd(II), the value of k obtained 0.176 g.mg -1 .min -1 for activated bottom ash and 0.218 g.mg -1 .min -1 for dithizone immobilized bottom ash. The adsorption isotherm models for Pb(II) and Cd(II) ions on both adsorbent followed Freundlich isotherm model with the KF value on the adsorption of Pb(II) obtained 0.035 L.g -1 for activated bottom ash and 0.634 for dithizone immobilized bottom ash. On the adsorption of Cd(II), the value of KF obtained 0.019 L.g -1 for activated bottom ash and 0.024 L.g -1 for dithizone immobilized bottom ash . The value of KF indicate that the adsorption capacity of Pb(II) and Cd(II) increases by using adsorbent of dithizone immobilized bottom ash compare activated bottom ash.